2012
DOI: 10.1155/2012/291087
|View full text |Cite
|
Sign up to set email alerts
|

Low-Dose Radiation Activates Akt and Nrf2 in the Kidney of Diabetic Mice: A Potential Mechanism to Prevent Diabetic Nephropathy

Abstract: Repetitive exposure of diabetic mice to low-dose radiation (LDR) at 25 mGy could significantly attenuate diabetes-induced renal inflammation, oxidative damage, remodeling, and dysfunction, for which, however, the underlying mechanism remained unknown. The present study explored the effects of LDR on the expression and function of Akt and Nrf2 in the kidney of diabetic mice. C57BL/6J mice were used to induce type 1 diabetes with multiple low-dose streptozotocin. Diabetic and age-matched control mice were irradi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
39
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 42 publications
(39 citation statements)
references
References 33 publications
(33 reference statements)
0
39
0
Order By: Relevance
“…Expression of the above-mentioned antioxidants is regulated positively by the transcription factor Nrf2. We demonstrated previously that Nrf2 is upregulated in diabetic mice exposed to LDR (51,57). Therefore, we next determined whether the altered antioxidant expression in the DM/LDR and DM/Com groups was due to altered renal Nrf2 levels (Fig.…”
Section: Resultsmentioning
confidence: 90%
See 4 more Smart Citations
“…Expression of the above-mentioned antioxidants is regulated positively by the transcription factor Nrf2. We demonstrated previously that Nrf2 is upregulated in diabetic mice exposed to LDR (51,57). Therefore, we next determined whether the altered antioxidant expression in the DM/LDR and DM/Com groups was due to altered renal Nrf2 levels (Fig.…”
Section: Resultsmentioning
confidence: 90%
“…The available data suggest that preexposure to LDR reduces the incidence of alloxaninduced diabetes and also delays the onset of hyperglycemia in diabetes-prone nonobese diabetic mice (46,48). This protection is associated with the prevention of oxidative damage (51)(52)(53)57). Our previous study revealed that, in addition to antioxidative effects, LDR also prevents inflammation to protect against DN (43,51,55,56).…”
Section: Discussionmentioning
confidence: 94%
See 3 more Smart Citations